Pengaruh kompensasi, pelatihan kerja dan jenjang karir terhadap prestasi kerja melalui kepuasan kerja di RSUD Koja Jakarta Utara - Sugiono, Edi; Aini, Aini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this thesis is to analyze the effect of compensation, job training, and career path on job performance through job satisfaction at Koja General Hospital, North Jakarta. This research method includes quantitative descriptive research. The model was analyzed using the Structural Equation Model (SEM) using statistical software AMOS 22, SPSS AND EXCEL 2016. Data collection was carried out at Koja Hospital, North Jakarta, using a questionnaire, the data obtained were 170 respondents. The results obtained from this study are compensation, training, career paths have a direct effect on job satisfaction and job performance and compensation, training, and career paths affect job performance and their impact on job satisfaction.